Comparison of effect of static and dynamic core exercises on speed and agility performance in soccer players - Sever, O.; Zorba, E. (Isokinetics and Exercise Science, 2018)
OBJECTIVE: This study compared the effects of dynamic and static core training programs on soccer related speed, agility. anaerobic power tests, core stability tests and body composition measurements. METHODS: A Static (n= 14) and Dynamic (n= 13) training groups performed three 30 min sessions per week for 8 weeks while attending scheduled soccer training sessions. RESULTS: Sprint (10-30 m), agility (505 and Arrowhead), vertical and standing long jump scores did not increase in any groups. Neither group demonstrated difference in body composition measurements for repeated test scores and between group comparisons. Experiment groups improved dynamic and static core stabilization test scores while Control group did not change. CONCLUSIONS: The results indicate that both training types improved movement related measures of core stability which did not transfer into any anaerobic skills and body composition. Thus core stability training is not generating sufficient stimulus to improve power and strength dependent performance skills such as sprint and agility and therefore may not constitute a cardinal component in soccer conditioning programs. ABSTRACT FROM AUTHOR